Identifying and ranking indicators affecting the environment with the aim of providing a guide on the establishment and operation of exhibition sites using BWM multi-criteria decision making method - Davoud Adineh; Reza Amirnezhad; Keyvan Saeb; Aptin x Aptin Rahnavard; Farid Gholamreza Fahimi (Anthropogenic Pollution)
The exhibition industry serves as a huge platform for face-to-face participation and the formation of potential economic and business relationships in the current century. These gatherings cost greatly in terms of energy resources are responsible for the emission of greenhouse gases and other pollutants into the water, air, and soil. The present study seeks to investigate and identify the pollutant indices resulting from the activities of the exhibition industry, its respective services and preparing guide on the organization of exhibition sites. For this purpose, the most important environmental criteria influenced by the industry were first identified through the Delphi method and were then classified into nine main priority groups based on multi-criteria decision-making and the best/ worst method(BWM[1]) method. The environmental index of the region was thus selected as the most important criterion whereas the social and economic indices were determined to be the least important criteria. Moreover, 58 sub-indices of the main indices were also weighed and prioritized based on the pairwise comparison. As a result, the sub-criterion of environmentally sensitive region ranked first while the sub-criterion of impact on the local and regional identity was identified as the least important influential sub-criterion. Weighing and prioritization of the indices were eventually the main foundation for the compilation of the exhibition site construction and operation instructions, and persistent monitoring of some indices such as the indoor air quality and consumed energy can reduce the negative environmental consequences of exhibition activities significantly.